Myth, Gender and Enterprise: Three Foundational Images of Costa Rican Contemporary Drama - Lázaro Girón, Luis (2014)
This article describes three fragmentary images on the origin of the Costa Rican drama from a contemporary point of view. Through these images it is shown that the Costa Rican theater lacks a native mythology, that female production comes late in its history, and that the Costa Rican theater emerges more as a political  and a entertainment necessity, than in relation to the development of the national dramatic literature.